Analysis of the Utilization of Scrum Framework Effort Estimation Metrics in Federal Public Administration - Kovags, Diego; Falchi, Fábio Luíz; Rivas, André Ronaldo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
The usage of agile software development methods is a reality in private and public organizations. However, the use of story points, a Scrum's typical metric for effort estimation has encountered resistance to its adoption in public administration, especially by regulatory authorities, once it varies according to the team's expertise. Thus, this paper aims to identify alternative metrics used by public administration to measure the effort in agile software development. From a documental research with qualitative approach, we analyzed the legal and normative framework of the federal sphere and we identified 57 software development contracts, whose metrics were analyzed. Hence, the main results showed that function points analysis remains being the most used metric, even in agile software development projects, due to their objectivity regarding functional requirements. However, the Technical Service Unit (UST) or related metrics has gained strength in agile software development projects, considering that it is indispensable to use a service catalog prepared at the contracting planning stage, as preconized by Brazilian Federal Court of Accounts (TCU) in its Judgment 2.362/2015.